Sistem Informasi Penjualan Pada Toko Al-Idan Variasi Motor Kelurahan Karang Baru, Kecamatan Mataram - Yulia Arianti; Maulana Ashari (LPPM STMIK Lombok, 2018)
Current trends online shopping via the Internet has mushroomed in Indonesia, even very well known by the general public. The many diverse ease of shopping and various kinds of goods and services offered, making the online shop to make Indonesian society as one of the